2011
DOI: 10.1128/aac.01016-10
|View full text |Cite
|
Sign up to set email alerts
|

The Tea Catechin Epigallocatechin Gallate Suppresses Cariogenic Virulence Factors of Streptococcus mutans

Abstract: Streptococcus mutans, the primary etiologic agent of dental caries, possesses a series of virulence factors associated with its cariogenicity. Alternatives to traditional antimicrobial treatment, agents selectively inhibiting the virulence factors without necessarily suppressing the resident oral species, are promising. The anticariogenic properties of tea have been suggested in experimental animals and humans. Tea polyphenols, especially epigallocatechin gallate (EGCg), have been shown to inhibit the growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
242
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(249 citation statements)
references
References 72 publications
4
242
0
3
Order By: Relevance
“…These phenolic compounds are believed to be promising candidates as complementary therapeutics (6), since they can modify bacterial behavior by affecting bacterial motility (7,8,58), surface adhesion (9), biofilm formation (7,10), quorum sensing (11), and production of virulence determinants (12,13). Traditional medicinal approaches owe their significance to the bioactive components that have their origin in plant sources, and many are associated with routine dietary habits.…”
mentioning
confidence: 99%
“…These phenolic compounds are believed to be promising candidates as complementary therapeutics (6), since they can modify bacterial behavior by affecting bacterial motility (7,8,58), surface adhesion (9), biofilm formation (7,10), quorum sensing (11), and production of virulence determinants (12,13). Traditional medicinal approaches owe their significance to the bioactive components that have their origin in plant sources, and many are associated with routine dietary habits.…”
mentioning
confidence: 99%
“…The crude LDH was extracted according to Xu et al [28]. The crude LDH was then treated with GH12 at sub-MIC levels for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The control group was not treated with GH12. The RNA isolation and purification were conducted as described before [28]. First-strand cDNAs were synthesized using PrimeScript™ RT reagent Kit with gDNA Eraser (RR047A; Takara Bio, Shiga, Japan), according to the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of dentistry, it has also been reported that sub-MICs of antimicrobial agents or compounds can inhibit bacterial attachment [54,56,57], biofilm formation [54,55,57,58], and downregulate virulence genes [54,56,59,60]. Moon et al reported N-acetyl cysteine (NAC) that is an antioxidant possessing anti-inflammatory activities, showed a significant decrease of Prevotella intermedia biofilm formation in the presence of sub-MIC [55].…”
Section: Antimicrobials-induced Biofilm Formationmentioning
confidence: 99%